The Positive Impact of US-China Trade War on Global South's Position in the Global Value Chain - Basundoro, Alfin Febrian; Abrar, Muhammad Irsyad; Sanjaya, Trystanto (Journal of World Trade Studies, 2022)
Amid the US-China trade war, several US companies have relocated back to the US, while China turned its industry inward to become more self-sufficient. This unpleasant development created a risk for Global South’s position in the Global Value Chain (GVC), especially in countries with manufacturing industries that can only assemble products. However, throughout the last decade, the position of the Global South within the GVC has been strengthening. In 2016, the Global South produced more than 47% of global manufacturing exports. However, the US-China trade war has threatened the delicate process and connection of the GVC. The interference of American and Chinese governments in international trade has forced many companies in taking measures to reduce their exposure to political risk. Additionally, an increasing number of American companies are reconsidering their decision to invest in the Chinese market and diversifying their investment to the Global South. This paper argues that the trade war could provide opportunities for Global South countries, particularly Southeast and South Asian countries represented by India. These opportunities include broader employment access for the youth, robust industrial-based innovation, and rapid economic growth, leading to a higher national income and life quality improvements.